Improve the efficiency of electronics router device - Devendra Kumar Somwanshi and Dr. Mahaveer Singh Naruka (International journal of economic perspectives, 2018)
Study of data communication electronics router device in Computer Networks or data communication network is such a distinctive mobile computing optimal router device which is used in any computer networks and that can be come across in world applications of algorithms. The router is a physical or virtual internetworking device that is designed to receive, analyze, and forward data packets among the computer networks. A router examines a destination IP address of a given data packet, and it uses the headers and forwarding tables to decide the best way to transfer the packets between the networks.